God unlimited: Economic transformations of contemporary Nigerian Pentecostalism - Ukah, Asonzeh F. K. (Research in Economic Anthropology, 2011)
The last three decades of the 20th century was a period of momentous social, economic, political and religious turmoil in many African societies. Nigeria is a prime example. Although the economic transformations of this period were perhaps bigger than other kinds of change, religious shifts probably had more remarkable social effects. One particularly noticeable development was the emergence of a new strand of Pentecostalism that serves as a source of political power and as a vehicle for economic mobilisation. Embedded in a theology of materialism and a redefinition of 'money', this new ideology found a fertile ground among local and global corporations struggling to cope with problems such as a devalued currency and political corruption and instability. Using data from ethnographic research on the Redeemed Christian Church of God (RCCG), with more than 10,000 congregations worldwide, this chapter shows how the near economic meltdown of the last decades of the 20th century precipitated a massive religious (re)engagement with economic structures and practices in Nigeria. Copyright © 2011 by Emerald Group Publishing Limited.
Paid